Unspecific CTL Killing Is Enhanced by High Glucose via TNF-Related Apoptosis-Inducing Ligand - Yang, Wenjuan; Denger, Andreas; Diener, Caroline; Küppers, Frederic; Soriano-Baguet, Leticia; Schäfer, Gertrud; Yanamandra, Archana K.; Zhao, Renping; Knörck, Arne; Schwarz, Eva C.; Hart, Martin; Lammert, Frank; et al. (Frontiers in Immunology, 2022)
TNF-related apoptosis inducing ligand (TRAIL) are expressed on cytotoxic T lymphocytes (CTLs) and TRAIL is linked to progression of diabetes. However, the impact of high glucose on TRAIL expression and its related killing function in CTLs still remains largely elusive. Here, we report that TRAIL is substantially up-regulated in CTLs in environments with high glucose (HG) both in vitro and in vivo. Non-mitochondrial reactive oxygen species, NFκB and PI3K/Akt are essential in HG-induced TRAIL upregulation in CTLs. TRAILhigh CTLs induce apoptosis of pancreatic beta cell line 1.4E7. Treatment of Metformin and Vitamin D reduces HG-enhanced expression of TRAIL in CTLs and coherently protects 1.4E7 cells from TRAIL-mediated apoptosis. Our work suggests that HG-induced TRAILhigh-CTLs might contribute to destruction of pancreatic beta cells in a hyperglycemia condition.